Conflict resolution in post-conflict DRC, Rwanda and Sierra Leone : towards a synergy of the rights-based and interest-based approaches to conflict resolution - Viljoen, Frans (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.